The Effect of Binahong Leaves (Anredera cordifolia Steenis) Extract on Blood Urea Nitrogen (BUN) Creatinine Serum and Renal Histopathology of Male White Rats (Rattus norvegicus) with Diabetes Mellitus - Tandi, Joni; Patala, Recky; Towulu, Dessy Gracelia; Lidongi, Putri Marcelita; Handayani, Tien Wahyu; Kanan, Maria (Majalah Obat Tradisional, 2023)
Diabetic nephropathy is one of the complications of diabetes mellitus on the pancreas that can end up in chronic pancreas failure. Various treatment options to repair pancreas damage due to diabetic nephropathy, one of which is by using Anredera cordifolia leaves. This study aims to determine the content of secondary metabolites in Anredera cordifolia leaves ethanol extract, and to determine the effective dose of Anredera cordifolia leaves ethanol extract in regenerating male white rat kidney cells. This study uses a laboratory experimental method. This study used 30 rats divided into 6 treatment groups, each group consisting of 5 test animals, namely normal group, negative control, positive control, dose of 25 mg/kg BW, dose 50 mg/kg BW, and dose 100 mg/kg bw. The level of histological damage to the renal tubules was observed with HE staining using an Olympus CX23 microscope. The data from the scoring of the level of renal tubular damage were analyzed using the Kruskal-Wallis test followed by the Mann-Whitney test to see the differences between treatments. The results showed that the Anredera cordifolia leaves ethanol extract contained secondary metabolites of alkaloids, flavonoids, saponins, and tannins; Anredera cordifolia leaves ethanol extract has an effect on kidney cell repair; Anredera cordifolia leaves ethanol extract at a dose of 100 mg/kg bw is effective reducing urea and creatinine; with an average decrease of 17.0 and 0.71 mg/dL in repairing kidney cells with an average damage value of 1.